An analysis of group formation process in statistics course with cooperative model. (October 2020) - Kosasih, U; Haerani, T; Nurjanah, N; Rahman, S A
Abstract: Good group formation gives students enthusiasm for mathematics learning. Group formation often results in mathematics learning discomfort. Therefore, the mathematics teacher needs to review ways to form study groups. This study examines ways to create groups that are in line with student needs. This type of research is a qualitative study with the subject being a junior high school student. The instruments used were tests and interview guides. Based on the data obtained, this study concludes that there are two ways of forming learning groups, namely grouping by number-grouping and independent-grouping. One of the two methods is more effective in achieving learning objectives.